Desenvolvimento de uma proposta de ensino CAD com uma abordagem universal para estudantes de engenharia - Pereira, Diego Andrade (2025)
In the current context of industrial engineering, computational tools are becoming more decisive for achieving the competitiveness demanded by the market. In this regard, CAD tools represent an important link between the initial conceptions of a project and the product's life cycle. It is believed that with the range of CAD solutions available, migration and adaptation between software represents a obstacle encountered by design drafters. Along with this factor, it is known that the availability of didactic literature addressing this topic is not proportional to the advancement of this technology in recent decades. Given what was proposed above, the present work aimed to analyze a CAD teaching proposal with a universal approach focusing on primitive fundamentals, which are common to various software programs focused on the field of industrial design for engineering. The development of the proposal was guided by the product design methodology of Pahl et al. (2005) with specific adaptations. The developed didactic proposal was tested in a classroom setting by a total of twenty-eight students distributed across five classes. Each class used a different software: Inventor, Fusion 360, Creo Parametric, Onshape, and SolidWorks. Participating students were evaluated through a questionnaire with questions related to the researched themes. The indicators showed a 96.3% index regarding the adaptability of the teaching proposal in relation to the software used. They also demonstrated significant improvements in students' confidence level for modeling 3D parts, in the understanding of technical drawing, and knowledge of important CAD terms, The results indicated that the proposal was effective for the training conducted and represents a new alternative in teaching of parametric drawing subjects for engineering courses such as mechanical, agricultural, electrical, production, among others.